(untitled) - Nayyeri, Keyvan (Indianapolis, IN, 2008)
Whether you want to integrate optimized builds, enhanced programming tools, or other rapid application development features, this unique resource shows you how to develop customized extensions. After a quick introduction of basic concepts, this book delves into the automation model and add-in development with the help of a case study, numerous examples, and sample code. You?ll discover how to take advantage of the Add-in Wizard, manipulate solutions and projects, work with text in documents and programming code, create Tool Options Pages, and more
Keywords: Microsoft Visual studio,Application software,Microsoft Visual studio,Phần mềm ứng dụng; Development,Phát triển